ANALISIS PENGARUH HARGA, PROMOSI, DAN PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN JASA RENTAL MOBIL DI SURAKARTA - Hestin Mutmainah, Budi Istiyanto C. Hendratmoko (MAJALAH ILMIAH GEMA, 2015)
These days the level of competition in the business world is increasing. This condition requires business players to be creative and innovative in order to ind a solution or appropriate strategies to achieve competitive advantage in the hope that the company can survive and win the competition. Car rental services business must also have its own marketing strategies that are considered good for business development. The strategy will include: competitive pricing, selecting an effective media campaign, and provide quality service. This research was carried out on a car rental service users who are in Surakarta. Samples taken a total of 120 respondents are accidental (accidental sampling.) Formulation of the problem: (1) Is there an inluence of The Price on the Purchase Decision of Car Rental Service in Surakarta. (2) Is there an inluence of the Promotion on the Purchase Decision of Car Rental Service in Surakarta. (3) Is there an inluence of the Services on Purchase Decision of Car Rental Service in Surakarta. (4) Among Price , Promotion, and Services which the dominant variable in inluencing the purchase decision Car Rental Service in Surakarta. Analysis using: test instrument data, the classical assumption, and multiple linear regression analysis (t test, F test, and the coeficient of determination). The results showed that: (1) Variable price, promotion, and services partially andsimultaneously signiicant effect on the purchase decision. (2) Variable services have a dominant inluence compared to the variable price and promotion on purchase decision. (3) The coeficient of determination is 61.1 percent. This means that the variation of price, promotion, and services are able to explain the variation of the purchase decision of 61.1 percent, and the remaining 38.9 percent of the variation of the purchase decision is explained by other variables outside the model. It is important for The Car Rental Company to give priority to good service to its customers because of this factor becomes a major consideration for them in their purchase decision. In addition, it is also important for the company to keep doing aggressive promotions and to determine competitive rental rates. Keywords: price, promotion, services, purchase decision